Solution of Breach of Contract Litigation in Overmavcht on Mudharabah Contracts in BMT - Khoiriyah, Fitrotul; Ashlihah, Ashlihah; Hermawan, Rudi (Et-Tijarie, 2023)
The purpose of this study is to analyze the settlement of wanprestasi disputes due to the overmacht factor in the Mudharabah contract.The type of research used is qualitative research that uses field observation methods. The object of this research is BMT Al-Hikmah Semesta, Jepara, Indonesia. Meanwhile, the subject of this study is the settlement of wanprestasi disputes. Data collection was carried out through observation, interview, and documentation techniques. In this study, the researcher selected informants as data sources, collected data, researched data quality, interpreted the data and made conclusions on his findings.The results of this study found that the settlement of disputes against customer members who committed wanprestasis by means of peace/family.